RETRACTED ARTICLE: Melatonin levels and embryo quality in IVF patients with diminished ovarian reserve: a comparative study - Yingying Wang; Shangjie Liu; Feifei Gan; Dan Xiong; Xiuming Zhang; Zhou Zheng (Reproductive Biology and Endocrinology)
Abstract Background Melatonin, a hormone found in various bodily fluids and cells, is known for its potent antioxidative, anti-apoptotic, and endocrine regulatory properties. This study aimed to analyze melatonin levels in patients with diminished ovarian reserve (DOR) and its impact on embryo quality. Methods We enrolled 85 women who were undergoing in vitro fertilization or intracytoplasmic sperm injection procedures, including normal ovarian reserve (NOR, n = 27), pathological DOR (DOR-Path, n = 25), and physiological DOR (DOR-Phy, n = 33). Melatonin levels in patient serum and follicular fluid were assessed using ELISA, and correlations between melatonin levels and indicators of embryo quality were examined. Results Our findings indicate that melatonin levels in the follicular fluid and basal serum of the DOR-Path and DOR-Phy groups were lower compared to the NOR group (P < 0.05). However, no significant differences in melatonin levels were found between the DOR-Path and DOR-Phy groups (P > 0.05). Additionally, the concentration of melatonin in the follicular fluid of the NOR group was significantly higher than in their serum (P < 0.001). Lastly, a significant correlation was discovered between melatonin levels in serum and follicular fluid and parameters of ovarian reserve and embryonic development (P < 0.05). Conclusions Melatonin levels in DOR patients may impact embryo quality, offering insights into potential DOR pathogenesis and opportunities to enhance treatment outcomes in these patients.